Critical Issues in Open and Distance Education Research - Xiao, Junhong (International Review of Research in Open and Distributed Learning, 2023)
Despite its mainstreaming into the broader educational ecology, open and distance education (ODE) still leaves much to be desired in terms of both practice and research. Inspired and informed by the author’s 35 years of experience as an ODE practitioner, researcher, reviewer, and editor, this article concentrates on 10 critical issues of ODE research that have long existed but may have a consequential impact on its healthy growth. The issues discussed cover scarcity of longitudinal research, paucity of scaling-up and generalization research, preference for success over failure presented in research, the need for a systems approach, lack of sociocultural sensitivity, technologization of research, scant attention to ODE for the underprivileged and disadvantaged, insufficient research on ODE policy, negligence of historical research, and disinterest in revisiting ODE theories. The causes of these problems are critically interpreted and their possible negative impacts on the field of ODE are explored in a concise manner. The purpose of this article is to encourage further discussion and debate on ODE research to sustain its presence and acceptance as a legitimate mode of education in the wider educational community.